2004
DOI: 10.1016/j.trstmh.2003.12.011
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection among paediatric in-patients in Blantyre, Malawi

Abstract: To investigate the impact of HIV infection on hospital admission and death we studied children admitted to paediatric medical and surgical wards in Blantyre, Malawi, in March 2000. Unselected children whose parents or guardians consented to HIV testing of the child were recruited and HIV infection was determined by serology, with confirmation in children aged 15 months or less by PCR. We assessed the prevalence of HIV infection by age, clinical diagnosis and outcome of admission. Of 1064 admissions, 991 were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 30 publications
4
37
0
Order By: Relevance
“…7 Paediatric inpatient programmes were the most common context (17), 6,7,10,[13][14][15][16][17][18][19][21][22][23][24][25]29,30 followed by nutrition centres (four), 9,11,12,27 EPI centres (three), 20 programmes (three). 8,20,31 The assessment for quality showed that most of the included studies (20) [9][10][11][12][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31] were of fair or good quality and the remainder (six) [6][7][8]13,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Paediatric inpatient programmes were the most common context (17), 6,7,10,[13][14][15][16][17][18][19][21][22][23][24][25]29,30 followed by nutrition centres (four), 9,11,12,27 EPI centres (three), 20 programmes (three). 8,20,31 The assessment for quality showed that most of the included studies (20) [9][10][11][12][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31] were of fair or good quality and the remainder (six) [6][7][8]13,…”
Section: Resultsmentioning
confidence: 99%
“…We did a stratifi ed analysis of paediatric HIV prevalence in southern and eastern Africa (20 studies) 8,[10][11][12][13][14][15][16][17][18][19][20][21][22][24][25][26][27]28,29 versus that in west and central Africa (four). 9,23,28,31 Paediatric HIV prevalence across contexts in southern and eastern Africa was 17路8% (95% CI 12路8-22路7) and prevalence in west and central Africa was 9路8% (95% CI 4路2-15路3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we identified a significant association with oral candida, this occurred in over 20% of uninfected children, making it an unreliable marker of HIV infection in SAM. Candida is commonly cited as associated with HIV (2,13,(22)(23)(24). Many studies have found persistent diarrhoea to be much more common in paediatric HIV (2, 25, 33) with a relative risk of 6.1 reported on the wards in Blantyre (2).…”
Section: Clinical Signs Predictive Of Hivmentioning
confidence: 99%
“…Chronic suppurative otitis media (CSOM) has been reported as more common in HIV infection, both on pediatric wards (2), and in the NRU (24).…”
Section: Introductionmentioning
confidence: 99%